2020
DOI: 10.1073/pnas.2006470117
|View full text |Cite
|
Sign up to set email alerts
|

An ATP-dependent partner switch links flagellar C-ring assembly with gene expression

Abstract: Bacterial flagella differ in their number and spatial arrangement. In many species, the MinD-type ATPase FlhG (also YlxH/FleN) is central to the numerical control of bacterial flagella, and its deletion in polarly flagellated bacteria typically leads to hyperflagellation. The molecular mechanism underlying this numerical control, however, remains enigmatic. Using the model species Shewanella putrefaciens, we show that FlhG links assembly of the flagellar C ring with the action of the master transcriptional reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(59 citation statements)
references
References 44 publications
(53 reference statements)
2
50
0
Order By: Relevance
“…In agreement with cryo–electron tomography studies, the data indicate that, in the S. oneidensis motor, eleven stators can be synchronously engaged ( Kaplan et al, 2019 ; Blagotinsek et al, 2020 ). In the presence of Na + , eight of the 11 positions are occupied by the Na + -dependent PomAB stator.…”
Section: The Dynamic Hybrid-fueled Motors Of Shewanella One...supporting
confidence: 84%
“…In agreement with cryo–electron tomography studies, the data indicate that, in the S. oneidensis motor, eleven stators can be synchronously engaged ( Kaplan et al, 2019 ; Blagotinsek et al, 2020 ). In the presence of Na + , eight of the 11 positions are occupied by the Na + -dependent PomAB stator.…”
Section: The Dynamic Hybrid-fueled Motors Of Shewanella One...supporting
confidence: 84%
“…It would be interesting to study whether a similar regulatory mechanism exists in V. parahaemolyticus . We find it noteworthy that FlhG directly interacts with a transcriptional regulator ( Blagotinsek et al, 2020 ) and we speculate that perhaps its localization in non-polar foci, which we observe in the absence of HubP, could be related to its function in transcriptional regulation and possibly reflect an interaction with transcriptional regulators on the chromosome – hereby giving rise to the distinct focus localization sites that are particularly enhanced in the absence of HubP in V. parahaemolyticus . In this way, we would like to hypothesize that the localization of FlhG to the cell pole might not only reflect a function in regulating FlhF activity, but possibly to sequester it spatially to prevent its action on transcriptional regulation in the cytoplasm as a specific cell cycle check point.…”
Section: Discussionmentioning
confidence: 69%
“…In V. cholerae , both FlhF and FlhG are known transcriptional regulators of flagellar genes ( Correa et al, 2005 ). Indeed, very recently it was shown that FlhG plays a very direct role in regulating the expression of flagellum genes in S. putrefaciens by connecting the initial phases of flagellum formation with the activity of the transcriptional regulator FlrA ( Blagotinsek et al, 2020 ), which in V. parahaemolyticus is referred to as FlaK. It would be interesting to study whether a similar regulatory mechanism exists in V. parahaemolyticus .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to analyze if changes seen for translation inhibition were specific for Ffh, FtsY, and ribosomes, we visualized the dynamics of a protein that is unrelated to translation. We chose the enhancer binding protein FlrA, which plays an important role in gene regulation for establishment of the single polar flagellum in Shewanella (Blagotinsek et al, 2020). FlrA is a hexameric AAA + protein that influences RNA polymerase activity (Gao et al, 2020).…”
Section: Ffh and Ftsy Mobilities Change In Response To Inhibition Of Transcription Or Of Translationmentioning
confidence: 99%